Thermal and Chemical Investigation of Some Fatty AcidsSubjected to Accelerated Thermal Cycle - Sari, Hayati; Sari, Ahmet (Asian Journal of Chemistry, 2010)
Thermal and chemical investigations of the lauric, myristic, palmitic and stearic acids as latent heat storage materials subjected to accelerated thermal cycles (400, 700 and 1000 meltfreeze cycles) were carried out. The latent heats of fusion and melting temperatures of the fatty acids with industrial grade (90–97% purity) as functions of thermal stability after the repeated thermal (heating-cooling) cycles were measured by differential scanning calorimetry (DSC) technique. The DSC analyses showed that the decrease in the latent heats of fusion and the melting temperatures of the fatty acids are in the range of about 9–17.1% and 1.5–2.6ºC, respectively during 1000 thermal cycles. The probable reasons for the decrease in these thermal properties were searched by Fourier transform infrared (FTIR) spectroscopic and potentiometric titration methods. The FTIR spectra and pKa values with respect to the thermal cycle number indicated that the decrease in the thermal stability of the acids may be due to the amount of impurity in the acids.